2007
DOI: 10.1002/jlcr.1388
|View full text |Cite
|
Sign up to set email alerts
|

The use of biocatalysis in the synthesis of labelled compounds

Abstract: Since most biotransformations are highly chemo-, regio-and stereoselective, they offer many opportunities for the synthesis of compounds that are not easily attainable by classical organic chemistry, The catalytic properties of the cytochrome P450 (CYP450) enzymes of microorganisms can be exploited to produce suitable N-, S-or Odealkylated precursors, which can be realkylated with the appropriate labelled reagent. These enzymes are also well reported for hydroxylation of activated or nonactivated carbon centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…An example is the synthesis of 1 0 -hydroxy[ 13 C 4 ]midazolam (31) 39 Hydrolysis of the nitriles 36a and 36b 44 by an immobilized enzyme system (nitrilase/ amidase activity) prepared from Rhodococcus sp. An example is the synthesis of 1 0 -hydroxy[ 13 C 4 ]midazolam (31) 39 Hydrolysis of the nitriles 36a and 36b 44 by an immobilized enzyme system (nitrilase/ amidase activity) prepared from Rhodococcus sp.…”
Section: Transformations Of Functional Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…An example is the synthesis of 1 0 -hydroxy[ 13 C 4 ]midazolam (31) 39 Hydrolysis of the nitriles 36a and 36b 44 by an immobilized enzyme system (nitrilase/ amidase activity) prepared from Rhodococcus sp. An example is the synthesis of 1 0 -hydroxy[ 13 C 4 ]midazolam (31) 39 Hydrolysis of the nitriles 36a and 36b 44 by an immobilized enzyme system (nitrilase/ amidase activity) prepared from Rhodococcus sp.…”
Section: Transformations Of Functional Groupsmentioning
confidence: 99%
“…Remethylation under standard conditions demonstrated that 57 was a precursor suitable for carbon-11 (and therefore probably tritium or carbon-14) labeling 39 . As recently communicated, SSR126768 (56) was demethylated by incubation with Mortierella isabellina MMP108 to obtain the required SSR1136660 (57).…”
Section: Dealkylation-realkylation Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] The direct singlestep/one-pot transformation of parent drugs would be a challenging but highly efficient alternative approach for the preparation of difficult accessible metabolite structures. On preparative scale, besides conventional chemical oxidation, [16][17][18][19] biomimetic catalysis, [20][21][22][23][24] electrochemical oxidation 25 and also microbial transformations 26,27 have been applied for the oxyfunctionalization of drug molecules. However, existing chemical methods for direct oxygen incorporation into organic molecules are often accompanied by low yields and specificities whereas whole-cell biotransformation processes typically require specific fermentation know-how and equipment.…”
Section: Introductionmentioning
confidence: 99%
“…The syntheses of unlabelled, stable‐labelled, and tritium‐labelled midazolam have been detailed in the literature 7–9. The use of carbon‐14‐labelled midazolam in metabolism studies has also been reported 10–12.…”
Section: Introductionmentioning
confidence: 99%